2021
DOI: 10.1177/10901981211011938
|View full text |Cite
|
Sign up to set email alerts
|

Reasoned Action Approach Correlates of Fruit and Vegetable Diet Among African American Men Living With HIV: A Cross-Sectional Study

Abstract: Epidemiological evidence of the protective role of fruits and vegetables for a host of chronic health conditions is well-documented. However, there is a dearth of studies examining predictors of fruit and vegetable intake among African American men living with HIV. We report secondary analyses—multiple regression and logistic regression models fitted to examine the strength of the relationships between the reasoned action approach constructs; namely, attitudes, subjective norms, descriptive norms, self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…This demonstrates that along with improvement in nutrition knowledge and understanding the link between nutrition and health, based on the health belief model, the participants in the intervention group expressed greater confidence in making changes to promote positive health outcomes compared to the control group. A cross-sectional study conducted by Kelly and colleagues [ 40 ] found that self-efficacy was positively associated with meeting the recommendation guidelines for fruit and vegetable intake among PLWH. They concluded that interventions should target self-efficacy to effectively increase fruit/vegetable intake in PLWH and address the perceived benefits of meeting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that along with improvement in nutrition knowledge and understanding the link between nutrition and health, based on the health belief model, the participants in the intervention group expressed greater confidence in making changes to promote positive health outcomes compared to the control group. A cross-sectional study conducted by Kelly and colleagues [ 40 ] found that self-efficacy was positively associated with meeting the recommendation guidelines for fruit and vegetable intake among PLWH. They concluded that interventions should target self-efficacy to effectively increase fruit/vegetable intake in PLWH and address the perceived benefits of meeting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies conducted in China and Canada report insufficient fruit and vegetable intake, with 55.2% of the labor force and 40.7% of students falling short of recommended levels, showing no significant differences between urban and rural populations in the proportion of insufficient vegetable intake ( 10 ). A study conducted in Portugal among HIV-infected adults also indicated the low frequency of fruit and vegetable consumption, in which 42.5 and 23.7% of participating individuals consumed FAVs less than once per day ( 11 ). In Africa, studies indicate that only a small proportion of people consume and meet the recommended amount.…”
Section: Introductionmentioning
confidence: 99%